2012
DOI: 10.2174/1874091x01206010023
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase A Subunit α Catalytic and A Kinase Anchoring Protein 79 in Human Placental Mitochondria

Abstract: Components of protein phosphorylation signalling systems have been discovered in mitochondria and it has been proposed that these molecules modulate processes including oxidative phosphorylation, apoptosis and steroidogenesis. We used electrophoresis and Western blots probed with specific antibodies to protein kinase A α catalytic subunit (PKAα Cat) and A kinase anchoring protein of approximately 79 kDa molecular weight (AKAP79) to demonstrate the presence of these two proteins in human placental mitochondria.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…PKA pathway activation plays a major role in steroidogenic gene regulation in human placentas [ 55 ]. PKA is also located in mitochondria and regulates mitochondrial protein phosphorylation [ 56 ]. IGF-1 plays a critical role in fetal and placenta growth and development [ 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…PKA pathway activation plays a major role in steroidogenic gene regulation in human placentas [ 55 ]. PKA is also located in mitochondria and regulates mitochondrial protein phosphorylation [ 56 ]. IGF-1 plays a critical role in fetal and placenta growth and development [ 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Since the 1970s, it has been shown that PKA associates with, and in, mitochondria [ 85 – 88 ]. While catalytic subunits of PKA are predominantly found in the mitochondrial outer membrane [ 89 ], there is much evidence that PKA localizes to the mitochondrial inner membrane and matrix as well [ 87 , 90 93 ]. In general, PKA is concentrated in cellular membranes and organelles through interactions with A kinase anchor proteins (AKAPs) [ 94 , 95 ].…”
Section: Kinases Localized In Mitochondriamentioning
confidence: 99%
“…The sub-mitochondrial distribution of PKA appears to depend on the tissue, cell-type, and method of detection utilized. Recently, Ma et al showed that PKA is present in human placental mitochondria (90) and sucrose density gradient separation showed that the catalytic (C) submit of PKA is predominantly found in the mitochondrial outer membrane. There is alsoconsiderable evidence that PKA is localized in the mitochondrial matrix (116, 123, 132).…”
Section: Camp Signaling In Mitochondriamentioning
confidence: 99%
“…There are numerous splice variants of AKAP1 (S-AKAP84, AKAP121, D-AKAP1 and AKAP149), which share an N-terminal core but have distinct C termini, identified in mitochondria. S-AKAP84 binds RII and a known mitochondrial target sequence (87); AKAP121 binds and targets RIIα to the cytoplasmic surface of mitochondria (52, 115); D-AKAP1, which is a novel type of AKAP interacting with both type I and type II regulatory subunits of PKA, contains the same mitochondrial targeting signal sequence as S-AKAP84 (66); and AKAP79 was found in placental mitochondria (91). In addition, localization of a second dual specific-AKAP (D-AKAP2), recognizing both RI and RII forms of PKA, showed predominantly mitochondrial immunostaining (142).…”
Section: Camp Signaling In Mitochondriamentioning
confidence: 99%